TEACHERS’ PEDAGOGIC COMPETENCE IN TEACHING ENGLISH AT SMAN 1 SANGGAR IN BIMA - Ma'rifatullah Ma’rifatullah; Andi Tenri Ampa; Awalia Azis (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2019)
The main problem in this study what are Teachers Pedagogic Competence in teaching English at SMAN 1 Sanggar in Bima. This study aims to determine the Teachers Pedagogic Competence in Teaching English at SMAN 1 Sanggar. The approach used in this research was descriptive research. Location of research at SMAN 1 Sanggar in Bima. This type of research was qualitative research, where  the process data collecting using observation and questionnaire. As for the analysis the author uses descriptive qualitative analysis techniques, namely written data, observations to the location of the location directly, so that in this case the researcher seeks to conduct research that is describing thoroughly about the actual situation. The subjects in this study were three English teachers at SMAN 1 Sanggar in Bima. From the results of the research that has been done, the writer can conclude that the teacher's Pedagogic competence in Teaching English has been done to the students quite well. The forms include: in terms of teachers understanding the characteristics of students it has been carried out using learning strategies, learning methods, and learning materials that are appropriate to the needs of students. For aspects of teachers understanding learning theory and learning principles that educate with effective and varied learning, for aspects of curriculum development carried out to design learning activities that fit the needs of students.